A frequency-based analysis of cutting force for depths of cut identification in peripheral end-milling. (15th May 2022) - Grossi, Niccolò; Morelli, Lorenzo; Scippa, Antonio; Campatelli, Gianni
Highlights: A method to identify depths of cut in 2.5-axis milling is proposed. Normalized frequency spectrum of total cutting force is exploited. The method does not require information about cutting direction or force coefficients. Analytical equations to predict cutting force spectrum are provided. The method could lay the ground for a force-based cutting parameters monitoring system. Abstract: This paper presents a novel approach to identify both radial and axial depth of cut in 2.5-axis peripheral milling operations using cutting force signals analysed in the frequency domain (i.e., cutting force spectrum). In detail, the method exploits the normalized cutting force spectrum, which is directly obtained through dedicated analytical formulations, to estimate depths of cut. The proposed approach is promising and differs from previous works since it does require nor the cutting force coefficients or cutting force direction neither a dedicated instrumentation. The developed method was numerically and experimentally validated in different cutting conditions. The results obtained show that depths of cut are identifiable with a maximum absolute error less than 0.4 mm, proving that the proposed approach could be a solid foundation for a force based cutting condition monitoring system in peripheral milling.